In other words, how much is \dfrac{\partial E}{\partial w_{jk}}?
where the error is defined as E = \dfrac{(T - L_k)^2}{2} , where T is the expected/target output
L_h = input
L_i = intermediate
L_j = intermediate
L_k = output
the output of each neuron would be:
L_{i}=\sigma (\sum w_{hi}L_{h}) = \sigma (net_i)
L_{j}=\sigma (\sum w_{ij}L_{i}) = \sigma (net_j)
L_{k}=\sigma (\sum w_{jk}L_{j}) = \sigma (net_k)
The output of the NN given the weights and the inputs is then:
L_{k}=\sigma(\sum w_{jk}\sigma(\sum w_{ij}\sigma(\sum w_{hi}L_{h})))
Now, just some derivatives that will come handy later on:
- \dfrac{\partial \sigma (x)}{\partial x} = \sigma (x)(1-\sigma (x))
- (\dfrac{\partial net_k}{\partial{ L_j}})=w_jk
Let's start from the Output neuron:
\dfrac{\partial E}{\partial w_{jk}} = \dfrac{\partial E}{\partial L_k}\dfrac{\partial L_k}{\partial w_{jk}}= (\dfrac{\partial E}{\partial L_k})(\dfrac{\partial \sigma (net_k)}{\partial w_{jk}})=(\dfrac{\partial E}{\partial{ L_k}}) ( \dfrac{\partial{ \sigma (net_k)}}{\partial net_k})(\dfrac{\partial{net_k}}{\partial w_{jk}})=
- (\dfrac{\partial E}{\partial{ L_k}})= \dfrac{\partial{(\dfrac{(T - L_k)^2}{2})}}{\partial{L_k}}=(T - L_k)(-1)=(L_k-T)
- (\dfrac{\partial{ \sigma (net_k)}}{\partial net_k})=\sigma (net_k)(1-\sigma (net_k)=L_k(1-L_k)
- (\dfrac{\partial{net_k}}{\partial w_{jk}})=L_j
hence:
\dfrac{\partial E}{\partial w_{jk}} =(L_k - T)\cdot{L_k(1-L_k)}\cdot{L_j}
Let's look at the previous layer (layer k):
E = \dfrac{(T - L_k)^2}{2} = \dfrac{(T -\sigma (net_k))^2}{2} = \dfrac{(T -\sigma (\sum w_{jk}L_{j}))^2}{2}
\dfrac{\partial E}{\partial w_{ij}} = \dfrac{\partial E}{\partial{ L_j}} [L_j(1-L_j)][L_i]
\dfrac{\partial E}{\partial{ L_j}}=(\dfrac{\partial E}{\partial{ L_k}})(\dfrac{\partial L_k}{\partial{ L_j}})=(\dfrac{\partial E}{\partial{ L_k}})(\dfrac{\partial \sigma (net_k)}{\partial{ L_j}})=(\dfrac{\partial E}{\partial{ L_k}})(\dfrac{\partial \sigma (net_k)}{\partial{ net_k}})(\dfrac{\partial net_k}{\partial{ L_j}})=(L_k - T) \cdot{L_k(1-L_k)} \cdot{w_{jk}}
hence:
\dfrac{\partial E}{\partial w_{ij}} = [(L_k - T) \cdot{L_k(1-L_k)} \cdot{w_{jk}}] \cdot{[L_j(1-L_j)][L_i]}
From this we see that for any other intermediate layer we have that:
\dfrac{\partial E}{\partial w_{xy}} = \dfrac{\partial E}{\partial L_z} \cdot{[L_y(1-L_y)][L_x]}
(where x and y are from intermediate layers)
\dfrac{\partial E}{\partial w_{hi}} = \dfrac{\partial E}{\partial L_j} \cdot{[L_i(1-L_i)][L_h]}
where the tricky bit is to compute $\dfrac{\partial E}{\partial L_x}, from the above steps we can see the following recurrence rule:
- \dfrac{\partial E}{\partial L_k} =(L_k-T)
- \dfrac{\partial E}{\partial L_j} =(L_k-T) \cdot{L_k(1-L_k)} \cdot{w_{jk}}
- \dfrac{\partial E}{\partial L_i} =(L_k-T) \cdot{L_k(1-L_k)} \cdot{w_{jk}} \cdot{L_j(1-L_j)} \cdot{w_{ij}}
Once we have \dfrac{\partial E}{\partial w_{xy}} we can use this value to increase/decrease the weight by that amount, all modulated by an \alpha
\Delta{w_{xy}}= -\alpha \dfrac{\partial E}{\partial w_{xy}}
and the new weight w' would be then:
w'_{xy} = w_{xy} + \Delta{w_{xy}}